ANALISIS TINGKAT PENDAPATAN DAN KETAHANAN PANGAN RUMAH TANGGA BERDASARKAN SKOR US-HFSSM - Prima Amanda Khairunnisa (CV. Denasya Smart Publisher, 2025)
Food insecurity is a significant issue that can drastically impact people's quality of life, especially low-income households. This study aims to analyze the relationship between household income levels and food security, based on United States Household Food Security Survey Module (US-HFSSM) scores. Using quantitative methods with a correlational analysis design, data were collected online through the distribution of US-HFSSM questionnaires to ten purposively selected respondents. These respondents varied in terms of residence, education level of the head of the household, and number of children. The study results revealed a concerning reality: of the ten households surveyed, four households were classified as having very low food security, two households as having marginal food security, one household as having low food security, and only three households as having high food security. The average income of respondents was IDR 15,680,000, with 60% categorized as low-income. All respondents acknowledged that income significantly impacts food security. Low-income households are often forced to choose cheaper, less diverse, and not always nutritionally balanced foods. This study underscores the significant impact of income on food choices and highlights the need for targeted interventions to improve food access, diversity, and quality for low-income groups.